Zuccagnia punctata Cav. essential oil into Poly(ε-caprolactone) matrices as a sustainable and environmentally friendly strategy Biorepellent against Triatoma infestans (Klug) (Hemiptera, Reduviidae) - López, Sandra (2021)
The main strategies against Triatoma infestans (primary vector responsible for the Chagasdisease transmission) are the elimination or reduction of its abundance in homes through the applicationof insecticides or repellents with residual power, and environmental management through theimprovement of housing. The use of plant-derived compounds as a source of therapeutic agents (i.e.,essential oils from aromatic plants and their components) is a valuable alternative to conventionalinsecticides and repellents. Essential oil-based insect repellents are environmentally friendly and providereliable personal protection against the bites of mosquitoes and other blood-sucking insects. Thisstudy investigates, for the first time to our knowledge, the potential repellent activity of Zuccagniapunctata essential oil (ZEO) and poly("-caprolactone) matrices loaded with ZEO (ZEOP) prepared bysolvent casting. The analysis of its essential oil from aerial parts by GC?FID and GC-MS, MS allowedthe identification of 25 constituents representing 99.5% of the composition. The main components ofthe oil were identified as ()-5,6-dehydrocamphor (62.4%), alpha-pinene (9.1%), thuja-2, 4 (10)-diene(4.6%) and dihydroeugenol (4.5%). ZEOP matrices were homogeneous and opaque, with thicknessof 800 140 m and encapsulation efficiency values above 98%. ZEO and ZEOP at the lowestdose (0.5% wt./wt., 96 h) showed a repellency of 33 and 73% respectively, while at the highest dose(1% wt./wt., 96 h) exhibited a repellent activity of 40 and 66 %, respectively. On the other hand, until72 h, ZEO showed a strong repellent activity against T. infestans (88% repellency average; Class V)to both concentrations, compared with positive control N-N diethyl-3-methylbenzamide (DEET).The essential oils from the Andean flora have shown an excellent repellent activity, highlighting therepellent activity of Zuccagnia punctata. The effectiveness of ZEO was extended by its incorporation in polymeric systems and could have a potential home or peridomiciliary use, which might help prevent, or at least reduce, Chagas? disease transmission.